Competition law and policy in the EU and UK - MacCulloch, Angus; Rodger, Barry J. (Milton Park, Abingdon, Oxon : Routledge, 2015)
'Competition Law and Policy in the EU and UK analyses how competition law affects business. The book expertly examines topics such as co-ordinated actions, pricing behaviour, take-overs and mergers, while this fifth edition has been updated to take into account recent developments, including: Comprehensive coverage of UK competition body reforms Integrated chapter by chapter coverage of policy developments throughout the book Increased coverage of the role of economics in competition law, public and private enforcement and intellectual propertyThis thorough and up-to-date textbook provides is a reliable classroom resource for students of competition law'--
'Competition Law and Policy in the EU and UK provides a clear guide to the general policies behind and the main provisions of EU and UK competition law, including topics such as private enforcement, anti-competitive agreements, cartels, mergers, and market investigations. The book's contents are tailored to cover all major topics in competition law, and the authors' clear and accessible writing style offers an engaging and easy to follow overview of the subject for course use. New features to help clarify topics and reinforce key points include: - chapter overviews and summaries highlight the key points to take away from each chapter to structure student learning - discussion questions facilitate self-testing and seminar discussions of the major issues covered in each chapter, to help reinforce understanding of these topics - further reading lists additional resources in order to guide research and develop subject knowledge The fifth edition of this textbook has been revised and updated to take into account all developments and changes in the law, presenting and contextualising the impact of key cases, and providing a useful glossary of competition terminology that will be invaluable to those studying this subject'--
Includes bibliographical references and index.
Keywords: Restraint of trade -- European Union countries; Restraint of trade -- United Kingdom; Antitrust law -- European Union countries; Antitrust law -- United Kingdom